FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA DI BEI - SURYA PRASETYO, HENDRA (Berkala Ilmiah Mahasiswa Akuntansi)
Company is an entity cannot separated from the societal environment (stakeholders), thus the company should capable to give the satisfactory services for the sake of stakeholders by means of satisfying the information needs related to the business activities of the company. The efforts of company in satisfying the information needs of stakeholders are not enough just by means of obligatory disclosures only, but, rather given the voluntary disclosures in annual reports. This research had the purpose to test the influential factors to the voluntary disclosures. The independent variables taken were company size, capital structure, public ownership, company age, and profitability. The research objects were the basic and chemical industrial companies listed in the Indonesian Stock Exchange in 2008-2010. Samples used in the research were as many as 18 basic and chemical industrial companies selected by the purposive sampling technique. Data sources were obtained from the annual reports given respectively in the period of 2008-2010. Data analysis technique used the multiple-linear-regression.The result of the research indicated that the company size had effect on the voluntary disclosures. Capital structure, public ownership, company age, profitability had no effects on the voluntary disclosures.